Cyclic olefin copolymer based microfluidic devices for biochip applications: Ultraviolet surface grafting using 2-methacryloyloxyethyl phosphorylcholine - Jena, Rajeeb K. (American Institute of Physics, 2012)
This report studies the surface modification of cyclic olefin copolymer (COC) by 2-methacryloyloxyethyl phosphorylcholine (MPC) monomer using photografting technique for the purpose of biointerface applications, which demonstrate resistance to both protein adsorption and cell adhesion in COC-based microfluidic devices. This is essential because the hydrophobic nature of COC can lead to adsorption of specific compounds from biological fluids in the microchannel, which can affect the results during fluidic analysis and cause clogging inside the microchannel. A correlation was found between the irradiation time and hydrophobicity of the modified substrate. Static water contact angle results show that the hydrophilicity property of the MPC-grafted substrate improves with increasing irradiation time. The contact angle of the modified surface decreased to 20 ± 5° from 88 ± 3° for the untreated substrate. The surface characterization of the modified surface was evaluated using x-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (FTIR spectroscopy). Attenuated total reflection-FTIR and XPS results show the presence of the phosphate group (P-O) on modified COC substrates, indicating that the hydrophilic MPC monomer has successfully grafted on COC. Finally, it was demonstrated that cell adhesion and protein adsorption on the MPC modified COC specimen has reduced significantly.